Modern Cooperative Governance in Indonesia: Policy Insights from Koperasi Usaha Mandiri, Belitung - MAYASARI, Dessy; LOKANTARA, I Gede Wyana (PT Keberlanjutan Strategis Indonesia, 2025)
The 2024 Modern Cooperative Assistance program at Koperasi Konsumen Usaha Mandiri was implemented over a four-month period with a focus on enhancing business management. The primary objective of this program was to guide cooperative administrators and members in optimizing internal resources and capabilities while enhancing the effective utilization of natural resources. This assistance program not only provided technical expertise but also fostered an ecosystem conducive to both institutional and individual growth within the cooperative. A quantitative approach was employed to assess the program’s effectiveness through survey questionnaires administered to cooperatives that received assistance. This assessment aimed to identify changes in governance, capital access, digital technology adoption, and business innovation. The collected data were analyzed using descriptive statistical methods to examine trends and patterns observed before and after the implementation of the assistance program. The assessment results indicated a substantial improvement in modern cooperative performance, as reflected in the increase of evaluation scores from 24.53 to 70.08. These findings suggest that the assistance program played a crucial role in transforming cooperatives into more competitive and innovation-driven entities. Therefore, this data-driven assistance strategy can serve as a foundation for future policy development aimed at enhancing cooperatives' adaptability to the evolving dynamics of the digital economy in a sustainable manner.